Unrecognized Lower Jaw Fracture in a Physically and Emotionally Abused Child - Jasna Peručić; Marko Tarle; Petar Đanić; Igor Čvrljević; Ivan Salarić (University of Zagreb. School of Dental Medicine, 2022)
Diagnosing child abuse still poses a challenge for healthcare professionals. We will present a case in which a physically and emotionally abused four-year-old boy had an undiagnosed lower jaw fracture for almost eight months. The child first presented with a perimandibular swelling and was treated with antibiotics prescribed by his doctor of dental medicine. After not having responded to antibiotic treatment, the boy was referred to the Department of Oral and Maxillofacial Surgery, accompanied by his birth mother. The deciduous mandibular molars with deep cavities were extracted since we thought that they were the reason for swelling. After several visits with his foster mother, the child was finally diagnosed with a lower jaw fracture and a psychosomatic disorder. Physical abuse by his birth parents was later on confirmed, and the consequences were insufficient growth, non perception of pain and reduced speech development. After having been with his foster mother for almost a year, the child learned to complain when he was in pain. This report emphasizes the importance of taking a detailed medical history along with a thorough clinical examination.